Understanding Tax Practitioners' Acceptance of the Coretax System: an Extended Technology Acceptance Model (TAM 2) Approach - Ade Erawati; Sekar Mayangsari (Al-Makki Publisher, 2026)
The implementation of the Coretax Administration System (CTAS) in Indonesia promises to simplify tax administration, but the transition period is marked by massive technical disruptions. After one year of running, the fundamental question is whether this system is really capable of speeding up the tax processing process. This study aims to evaluate the effectiveness of Coretax with a qualitative approach using an expanded and modified Technology Acceptance Model framework. Data was collected through in-depth interviews with eight tax practitioners in Jakarta, then analyzed with thematic analysis. The findings point to a paradox. In terms of perceived usability, the system is considered very effective due to the centralization of a one-stop portal, but very inefficient due to the instability of the central system and the loss of large-scale data processing features. In terms of ease of use, the system is easy for practitioners to adapt to, but is considered complicated for ordinary taxpayers. Despite the decline in output data quality and heightened concerns over data security, acceptance of the system has been maintained, driven by compliance with job demands, adherence to legal obligations, and an improved professional image. In conclusion, although the concept of Coretax integration is considered brilliant, the government is required to immediately optimize server capacity, restore bulk data processing features, and improve cybersecurity to achieve the promised administrative efficiency.